Between the Lines - Imam, Parvez (f-20 Communications, 2001)
Verzio FF Submission In 2000, New Delhi has witnessed a number of arrests of "illegal" immigrants from Bangladesh. Many of them were kept in detention for long periods and families were separated. Many were sent back to Bangladesh where the local authorities claimed that they were not aware of any deportations. “Between the Lines” is about these people denied on both sides of the border.